MANAJEMEN PENDIDIKAN KARAKTER DALAM KELUARGA - HASAN, ZUHASNI (Inovasi Pendidikan, 2017)
Education is not only about intelligence shrewdness, but also children characters’ building. Character is soul attribute, morals, sensibleness that can make someone looks different with somebody eles. Someone with character can be defined has nature and personality. So, character is identical with morals. Character or moral of someone is formed through educational process. Family is the first time where educational character begin. In order to get great education , it needs management steps. So, parents as the manager must be competent in leading the educational process in family like planning, organizing, actuating and controlling.Keyword: educational character,